More all-of-a-kind family - Taylor, Sydney, 1904-1978 (All-of-a-kind family, 2014)
The continuing adventures of five sisters growing up in a Jewish family in New York in the early twentieth century. Ella finds a boyfriend and Henny disagrees with Papa over her curfew; a single uncle findss romance; World War I approaches and the family heads to Rockaway Beach to avoid infection during an outbreak of infantile paralysis.